Case 3807: Onthophagus anthracinus Harold, 1873 (Insecta, Coleoptera, Scarabaeidae): proposed conservation of the specific name - Kohlmann, Bert; Arriaga-Jiménez, Alfonsina; Rös, Matthias (Bulletin of Zoological Nomenclature, 2020)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific name of a well-known dung beetle, Onthophagus anthracinus Harold, 1873, a junior primary homonym of Onthophagus anthracinus Faldermann, 1835. Onthophagus anthracinus Faldermann, 1835 was synonymized with Onthophagus histeroides Ménétriés, 1832, which in turn was included in the genus Caccobius Thomson, 1859. After its synonymization in 1846, the senior homonym was never again used as valid, thus meeting the criteria of Article 23.9.1.1, but the junior homonym has not been cited in enough works during the past 50 years to meet the criteria of Article 23.9.1.2 for automatic reversal of precedence of the two homonyms. For the sake of stability it is proposed that the Commission use its plenary power to allow use of Onthophagus anthracinus Harold, 1873 as valid despite its status as a junior primary homonym of Onthophagus anthracinus Faldermann, 1835.
Keywords: Nomenclature; taxonomy; Scarabaeidae; Onthophagus anthracinus; Onthophagus histeroides; Caccobius anthracinus; homonymy; reversal of precedence; dung beetles; scarabs; Neotropical Region